Irisin in coronary bypass surgery - Aydin, Suna; Catak, Zekiye; Eren, Mehmet Nesimi; Topal, Askin Ender; Aydin, Suleyman (Bentham Science Publishers B.V., 2018)
Introduction: In coronary bypass surgery, after cardiopulmonary bypass is initiated by arterial cannulation in the ascending aorta and venous cannulation through a single vein generally in the right atrium, the process of cooling the patient is started. Objective: There is a relation between cooling the patient and irisin, which is responsible for releasing heat. Therefore, the main objective of the present study is to explore how irisin concentrations and some other panel of myocardium injury in patients undergoing coronary artery bypass surgery. Methods: The blood samples collected before induction (T1), before bypass (T2), before (T3) and after (T4) removing the cross-clamp, upon admission to intensive care (T5), and at the postoperative 24 (T6) and 72 (T7) hours, and whether these concentrations are correlated with lactate levels classically used in monitoring this surgery. A total of biological samples, 23 from control individuals and 105 from bypass patients (14-16 samples for each timeframe) were analyzed to determine irisin, CK-MB, TnT and BNP levels by ELISA and lactate levels by lactate assay kit. Both lactate and irisin were seen to increase gradually from the time of induction to the removal of the cross-clamp. After the cross-clamp was removed and the patient was started to be warmed, both parameters began to decrease gradually and were restored to normal levels on the second and third post-operative days. The increase and decrease in irisin were found correlated with lactate levels. CK-MB, TnT and BNP alteration were similar to each other. Results: Based on these results, it is estimated that measurement of irisin along with lactate may prove to be a useful parameter in monitoring the coronary bypass surgery and irisin may be a significant marker of hypothermia. Beside CK-MB, TnT and BNP, measurements of irisin concentration in open heart surgery may also be useful parameters for the panel of myocardium injury. © 2018 Bentham Science Publishers.
Keywords: Coronary bypass surgeries; Hypothermia; Irisin; Lactate; Myocardium injury; Pituitary gland